2012
DOI: 10.1504/ijsnet.2012.047720
|View full text |Cite
|
Sign up to set email alerts
|

Distributed k-connected fault-tolerant topology control algorithms with PSO in future autonomic sensor systems

Abstract: Fault-tolerant topology control in Wireless Sensor Networks (WSNs) has drawn a significant amount of research interest and become a hot point. In this paper, we first propose a centralised k-connected fault-tolerant topology control algorithm with Particle Swarm Optimisation (PSO) called CKFTC-PSO. In CKFTC-PSO, we take both issues of node failure and power efficiency into consideration and give the mathematical model of k-connected faulttolerant topology control problem. Inspired by physics of Genetic Algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 31 publications
0
47
0
Order By: Relevance
“…This structure consists of multiple clusters. Each cluster includes one cluster head (CH) and a limited number of cluster members [39,40,41]. The CH s and cluster members are all regular MH s .…”
Section: Ad Hoc Network Structure and Hybrid Checkpointing Modelmentioning
confidence: 99%
“…This structure consists of multiple clusters. Each cluster includes one cluster head (CH) and a limited number of cluster members [39,40,41]. The CH s and cluster members are all regular MH s .…”
Section: Ad Hoc Network Structure and Hybrid Checkpointing Modelmentioning
confidence: 99%
“…The advantages of PSO over many other optimization algorithms are its implementation simplicity and ability to converge to a reasonably good solution quickly. In the past several years, PSO has been successfully applied in many researches and application areas (Carlos et al 2004;Liu et al 2010;Guo et al 2011;Shen et al 2011;Costas et al 2012;Guo et al 2012;Agrawal and Silakari 2013;Rada-Vilela et al 2013). It has been demonstrated that PSO can get better results in a faster and cheaper way compared with other methods.…”
Section: Basic Psomentioning
confidence: 99%
“…On the one hand, people enjoy the convenience brought by the abundant information on the network; on the other hand, they are also suffering from the puzzle of information explosion. For example, if you are not good at filtering useless information when searching for the information you need from within a large amount of information, a considerable amount of time is spent in filtering information [4][5][6][7], which leads to a significant increase in retrieval time.…”
Section: Introductionmentioning
confidence: 99%